Centro Tradicional de Negocios de Toluca, 2000-2010: ¿oportunidad o decadencia? - Luis Giovanni Ramírez Sánchez (Economía, Sociedad y Territorio, 2020)
This paper consists of the analysis of the vitality or decline of the Traditional Business Center of Toluca (CTN), based on key variables: population, employment, and marginalization. The objective of this text is to examine if the CTN remains a vibrant and attractive place for urban activities or if, on the contrary, it is on a declining path. Unfortunately, the results show that more than 65% of the Basic Geostatistical Areas (AGEB) of the CTN register some degree of decline. The action or inaction of government agencies and organized society can contribute to the rescue of the CTN or accelerate its decline.